Size Distribution of Mineral Dust Emissions From Sparsely Vegetated and Supply‐Limited Dryland Soils. Issue 22 (15th November 2021) - Webb, Nicholas P.; LeGrand, Sandra L.; Cooper, Brad F.; Courtright, Ericha M.; Edwards, Brandon L.; Felt, Christopher; Van Zee, Justin W.; Ziegler, Nancy P.
Abstract: Controls on the particle size distribution (PSD) of mineral dust emissions remain poorly understood. Under near‐idealized conditions, dust PSDs can appear invariant with wind friction velocity. However, dryland vegetation attenuates surface friction velocities, and soil crusting reduces the supply of loose erodible material and increases surface resistance to abrasion. Under such conditions, variability in saltation bombardment efficiency and intensity could have a large effect on dust PSDs. We present dust emission measurements from vegetated, supply‐limited aeolian systems that indicate the dependence of emission‐flux PSD on wind friction velocity. We find the fine fraction (<5 μm) of dust particles increases with friction velocity. Results suggest models that assume wind‐invariance of the emission‐flux PSD may not be generalizable for crusted soils with vegetation. There is a need for dust models to represent variability in emission‐flux PSDs for land management, air quality, and climate applications across vegetated and sediment supply‐limited drylands. Plain Language Summary: The size of dust particles emitted into the air during wind erosion determines how soils are affected and how dust influences air quality and climate. However, much remains unknown about how wind speed, soil properties, and vegetation influence the size of emitted dust at different locations. Some studies suggest that when land is unvegetated and soils are loose, the size of emitted dust does not change with wind speed. We measured the size of dust emitted from vegetated landscapes with soils that are crusted and have changing amounts of loose erodible sediment. We found that wind speed has a strong effect on the size of emitted dust particles. Stronger winds produced finer dust at sites with weaker soil crusts and more loose erodible sediment. Predictive models need to consider the changing size of emitted dust particles in different environments in order to more accurately assess wind erosion and dust impacts. Key Points: Dust emission flux particle size distribution is dependent on wind friction velocity over vegetated and crusted dryland soils Dust emission flux is enriched in fine (<5 μm) particles with increasing wind friction velocity Dust emission models need to represent variability in dust particle size distribution from sediment supply‐limited aeolian systems